(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Ansharieta R, Ramandinianto SC, Effendi MH, Plumeriastuti H. 2021. Molecular identification of blaCTX-M and blaTEM genes encoding extended-spectrum ß-lactamase (ESBL) producing Escherichia coli isolated from raw cow’s milk in East Java, Indonesia. Biodiversitas 22: 1600-1605. The emergence of extended-spectrum ?-lactamase (ESBL) producing bacteria and its increasing level has become public health issue. The presence of these bacteria in food of animal origin is quite alarming. The objective of this study was to detect and characterize Escherichia coli producing ESBL encoding genes, isolated from 200 raw cow milk samples in East Java, Indonesia. The results of this study showed that 70.5% of isolates were confirmed as E. coli, based on the morphological growth of colonies on the EMB Agar and biochemical IMViC tests. In this study, the double-disc synergy test (DDST) method was used to confirm the ESBL, and previously sorted out presumptively by using Aztreonam antibiotic disc. The antibiotics used were amoxicillin-clavulanate, ceftazidime, and cefotaxime for DDST. In addition, ESBL confirmation with Multiplex PCR method for blaCTX-M and blaTEM genes were done. The presence of ESBL-producing by E. coli isolated from raw cow’s milk in East Java were 2.12% (3/141). The PCR results showed that the double blaCTX-M and blaTEM gene harbored by 2 ESBL isolates and one blaTEM gene as many as 1 ESBL isolate. Thus, the findings of our study indicate that milk can be a good reservoir of bacteria carrying blaCTX-M and blaTEM ESBL resistance genes with the potential to affect human health.